Developing a Finite Element Model for Thermal Analysis of Friction Stir Welding (FSW) Using Hyperworks - Meyghani, B. (Springer, 2020)
The study undertakes a three-dimensional finite element analysis of the friction stir welding (FSW) process of 6061-T6 aluminium alloy. The analysis investigates the temperature distribution and the fundamental knowledge of the process with respect to temperature difference in the material to be welded. HyperMesh® and HyperView® solver have been used from Altair Hyperworks® to analyse the process. Different traverse and rotational speeds have been applied in the model. The results of the study create a better understanding for peak temperature distribution. In addition, the results illustrate that the peak temperature during welding increases as the rotational speeds rises and the effect of the transverse speed on the temperature is found to be insignificant. Finally, comparisons with some published papers has been done in order to compare the results of the different finite element packages and summarize the advantages and disadvantages of each software. © 2020, Springer Nature Singapore Pte Ltd.